Uterine bleeding in postmenopausal women - Grzechocińska, Barbara; Skórka, Bogusław (Menopause Review/Przegląd Menopauzalny, 2006)
Uterine bleeding in postmenopausal women is the reason for about 5% of visits to physicians. Their aetiology differs from bleeding in premenopausal women. Before menopause unopposed oestrogen stimulation may lead to endometrial proliferation, hyperplasia, submucosal leiomyomata, and endometrial polyps. In older women the commonest disorder is endometrial atrophy. Microerosions of the surface epithelium and subsequent local chronic inflammatory reaction trigger changes seen in chronic endometritis. Additional factors are systemic diseases such as cardiovascular disease, liver disease, leukaemia, homeostatic disorders (coagulation factor deficiency) and medications: anticoagulants, corticosteroids, herbal and other supplements with oestrogen action, selective serotonin reuptake inhibitors, tamoxifen and thyroid hormone replacement. Nevertheless, routine diagnosis should be made with the aim of ruling out endometrial cancer in every case of bleeding in postmenopausal women.